Legal Fluency in the Digitalization of Maritime Agency Service OPERATIONS (A Study of Legal Implications in the Implementation of My Pertamina Marine Services (MMS) at PT Pertamina Trans Kontinental) - Afan Aftory (Publikasi Indonesia, 2025)
Digitalization has become essential in today’s business landscape, with customer satisfaction remaining a key objective. The use of physical documents and wet signatures is no longer mandatory, as digital processes now offer reliable validation and legal compliance while streamlining repetitive tasks. Legal fluency is crucial—it means conveying legal messages clearly and ensuring actions, processes, or documents meet all applicable legal standards. In this context, PT Pertamina Trans Kontinental (PTK), a leading maritime service provider, successfully developed and implemented My Pertamina Marine Services (MMS) on December 10, 2024. This integrated agency service platform connects seamlessly with the Enterprise Resource Planning (ERP) system and Auto Collection Bank feature. Launched on September 25, 2024, MMS responds strategically to the demands for business process digitalization and automation in the maritime sector. Built using an agile iterative method, MMS leverages a service-based architecture and standardized API to ensure real-time interoperability between agency operations, ERP, and banking systems. This end-to-end integration automates ship activity records, billing, and payment reconciliation, significantly reducing manual work, minimizing errors, and improving the cash conversion cycle. Real-time dashboards provide actionable insights, enabling data-driven decision-making. MMS stands as a transformative model for maritime companies embracing digital operations and automation.